Circulating granulocyte lifespan in compensated alcohol‐related cirrhosis: a pilot study. Issue 17 (13th September 2016) - Potts, Jonathan R.; Farahi, Neda; Heard, Sarah; Chilvers, Edwin R.; Verma, Sumita; Peters, Adrien M.
Abstract: Although granulocyte dysfunction is known to occur in cirrhosis, in vivo studies of granulocyte lifespan have not previously been performed. The normal circulating granulocyte survival half‐time ( G − t ½ ), determined using indium‐111 ( 111 In)‐radiolabeled granulocytes, is 7 h. In this pilot study, we aimed to measure the in vivo G − t ½ in compensated alcohol‐related cirrhosis. Sequential venous blood samples were obtained in abstinent subjects with alcohol‐related cirrhosis over 24 h post injection (PI) of minimally manipulated 111 In‐radiolabeled autologous mixed leukocytes. Purified granulocytes were isolated from each sample using a magnetic microbead‐antibody technique positively selecting for the marker CD15. Granulocyte‐associated radioactivity was expressed relative to peak activity, plotted over time, and G − t ½ estimated from data up to 12 h PI. This was compared with normal neutrophil half‐time ( N − t ½ ), determined using a similar method specifically selecting neutrophils in healthy controls at a collaborating center. Seven patients with cirrhosis (six male, aged 57.8 ± 9.4 years, all Child‐Pugh class A) and seven normal controls (three male, 64.4 ± 5.6 years) were studied. Peripheral blood neutrophil counts were similar in both groups (4.6 (3.5 − 5.5) × 10 9 /L vs. 2.8 (2.7 − 4.4) × 10 9 /L, respectively, P = 0.277). G − t ½ in cirrhosis was significantly lower than N − t ½ in controls (2.7 ± 0.5 h vs. 4.4 ± 1.0 h, P = 0.007). Transient rises in granulocyte and neutrophil‐associated activities occurred in four patients from each group, typically earlier in cirrhosis (4–6 h PI) than in controls (8–10 h), suggesting recirculation of radiolabeled cells released from an unidentified focus. Reduced in vivo granulocyte survival in compensated alcohol‐related cirrhosis is a novel finding and potentially another mechanism for immune dysfunction in chronic liver disease. Larger studies are needed to corroborate these pilot data and assess intravascular neutrophil residency in other disease etiologies. Abstract : While granulocyte dysfunction is known to occur in cirrhosis, in vivo studies of granulocyte lifespan have not previously been performed. This pilot study examined the in vivo circulating granulocyte residency time in cirrhosis, finding this to be substantially lower compared with healthy controls. This is another potential mechanism contributing to immune dysfunction in chronic liver disease.